Enhanced Self-Control for the Prevention of Pornography of Student in Senior High School - Ahsanul Hafizh; Firman Firman; Netrawati Netrawati (International Journal of Applied Counseling and Social Sciences, 2021)
The lack of students' self-control led to the emergence of pornography. The phenomenon of pornography is a general term that refers to sexually explicit material that may be softcore or hardcore and can also be referred to as things that attempt to stimulate and increase sex drive with text and images. Self-control is the ability to organize, guide, regulate, and direct forms of behavior that can lead to positive consequences. The purpose of this study was to describe students' self-control at SMA N 1 Merbau. This research uses descriptive analysis. The research sample consisted of 128 students who were taken using purposive sampling technique. The instrument used was "Self-control scale in preventing pornography" with a reliability value of (0.888). The results showed that: most of the students as many as (65.6%) of the students had "moderate" self-control in the prevention of pornography, then a small proportion of students (2.3%) of students had "low self-control". "In the prevention of pornography. Furthermore, as many as (5.5%) students had “very high” self-control in preventing pornography and as many as (26.6%) students had “high” self-control in preventing pornography. The results of the study generally showed that students' self-control was in the medium category with a percentage of 65.6% and it needed to be improved in order to prevent pornography. The results of this research can be used as a basis for counseling teachers in providing guidance and counseling services to prevent student pornographic behavior in schools.